KAJIAN PELAYANAN TRANSPORTASI UMUM PADA BUS DAMRI DI KOTA SEMARANG - Puspitasari, Serly; Suwitri, Sri; Rengga, Aloysius (Journal of Public Policy and Management Review, 2013)
Semarang city is one example of a metropolitan city in Indonesia are experiencing growing inhabitants of significantly. The increasing number of population prompted the Government to improve public facilities to support the activities of daily. One of them public facilities that needs to be improved is on transportation. Perum DAMRI is one of the service company specializing in the field of transport,especially in the city of Semarang. To be competitive, Perum DAMRI acquire passenger must provide good service so passengers loyal to their company. Decline in the performance of services can have an impact on decreasing the number of passengers on board because the company can't keep the wishes of passengers. This may result in the transfer of passenger transport services in the use of Perum DAMRI to transport services on other similar companies.The purpose of this study was to assess the service provided by Perum DAMRI. The type used is descriptive qualitative, looking from 5 dimensions service. The results showed that 3 of the 5 dimensions of service quality assessment shows the value that less well among other things on dimensions of service direct evidence, responsiveness, and reliability. From the third dimension that have the worst assessment was the dimension of reliability (reliability) is about the consistency of schedule. From the third dimension that have the worst assessment was the dimension of reliability (reliability) is about theconsistency of schedule.